Penerapan Teori Kognitivistik dalam Pembelajaran PAI di SMA - Nurfajriani, Wiyanda Vera; Shah, Khaf; Suryana, Ermis; Karolina, Asri (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Many learning theories exist in the realm of education, with cognitive learning theory being one of the most commonly used, especially in Indonesia. This particular theory is considered quite effective in its practical application. The main aim of this research is to explore the implementation of cognitive learning theory in the context of PAI (Islamic Education) subjects at SMA N. Using descriptive qualitative methodology, this research explores the analysis of various resources such as books and scientific articles. The findings of this investigation demonstrate the efficacy of cognitive learning theory when used in the educational environment of t State Middle School, especially in the PAI subject area. This efficacy underscores the importance of educators' creativity in utilizing a variety of learning strategies, methodologies, and resources to ensure successful implementation of cognitive learning theory. In addition, it is very important for educators to recognize and overcome the limitations of cognitive theory to optimize the learning process.